The Effects of "Search Engine Optimization" on Marketing of Diving Companies in Bali - Karisma, Iola Astried; Darma Putra, I Nyoman; Wiranatha, Agung Suryawan (E-Journal of Tourism, 2019)
The strategic location of the island of Bali which is surrounded by sea has a great potential for people in Bali to establish a diving company. Some diving companies in Bali have made various strategies to compete offering diving tour packages. Marketing through the internet is the best way that most diving companies in Bali have recently taken. However, to be able to compete with other similar companies on the internet, the website must be easily accessible to internet users, i.e. by appearing on the first page of the Google search engine. SEO or search engine optimization is an internet marketing strategy that serves to increase website visibility by targeting certain keywords. The use of SEO can have a positive impact on increasing online sales, increasing website visibility and brand awareness on the internet. This study aims to analyze the extent to which SEO techniques have a positive impact on the marketing of diving tourism in Bali through the internet, using quantitative descriptive methods. The research was conducted in three selected companies, namely Bali Diving, Atlantis Dune, and Scuba Adventure. The results of the study showed that diving companies in Bali have obtained all the positive impacts of SEO. These impacts were increasing website visibility, brand awareness, and sales. Keywords: Diving in Bali, Internet Marketing, SEO, Bali Tourism.